Heparinase Digestion of 3-O-Sulfated Sequences: Selective Heparinase II Digestion for Separation and Identification of Binding Sequences Present in ATIII Affinity Fractions of Bovine Intestinal Heparins - Mourier, Pierre (Frontiers in Medicine, 2022)
Binding to antithrombin-III (ATIII) determines the anticoagulant activity of heparin. The complexes formed between heparin and ATIII result from a specific pentasaccharide sequence containing a 3-O- sulfated glucosamine in medium position. Building block analysis of heparins, following heparinase digestion, is a critical method in quality control that provides a simple structural characterization of a complex product. Hence, in these applications, study of the digestion of 3-O-sulfated moieties merits special attention. With heparinase II, specific inhibition of cleavage of the non-reducing bond of 3-O-sulfated units is observed. This specificity was erroneously generalized to other heparinases when it was observed that in exhaustive digests of heparins with the heparinase mixture, resistant 3-O-sulfated tetrasaccharides were also obtained from the specific ATIII-binding pentasaccharides. In fact, the detection of unsaturated 3-O-sulfated disaccharides in digests of heparin by heparinases I+II+III, resulting from the cleavage of the 3-O sulfated unit by heparinase I in non-conventional sequences, shows that this inhibition has exceptions. Thus, in experiments where heparinase II is selectively applied, these sequences can only be digested into tetra- or hexasaccharides where the 3-O-sulfated glucosamine is shifted on the reducing end. Heparinase I+II+III and heparinase II digests with additional tagging by reductive amination with sulfanilic acid were used to study the structural neighborhood of 3-O-sulfated disaccharides in bovine mucosal heparin fractions with increasing affinity for ATIII. The 3-O-sulfated disaccharides detected in heparinase I+II+III digests turn into numerous specific 3-O-sulfated tetrasaccharides in heparinase II digests. Additionally, ATIII-binding pentasaccharides with an extra 3-O-sulfate at the reducing glucosamine are detected in fractions of highest affinity as heparinase II-resistant hexasaccharides with two consecutive 3-O-sulfated units.